Comportamiento de paciente con cefalea asociada a forias horizontales. - Cañizares Herrera, Joseline Stefania (2020)
Headache behavior due to horizontal phoria is a refractory visual problem that produces hyperopia, due to close visualization as a result of prolonged work at the computer, since people who suffer from it need to strain the muscles of the eyes to maintain them parallel and see correctly. The phoria are latent deviations of the visual axes that appear due to the absence of the fusion stimulus, the eyes in the state of relaxation momentarily lose coordination, maintaining the visual stimulus without producing the integration of images in the brain. The main objective of this research work is to assess the behavior of a patient with headache associated with horizontal phoria. Within the clinical data that the patient refers is constant pain in both eyes at the time of visual effort and abnormal intolerance to light, which prohibits the development of their daily academic activities. When performing the optometric examination, he presents epiphora in the eyeball due to discomfort of natural and artificial light, the cover test will help to diagnose phorias or tropias, concluding with a definitive diagnosis of deviation of both eyes towards the nasal part. Especially the right eye. Due to the importance of the case, it is concluded that the headache is the product of the presence of phorias and endophoria in the patient due to the permanence of long periods of time in the computer and prolonged readings, the evaluation and refraction will receive the correction of the visual state by means of the design of a lens with light protection.